Prevalence and identification of Candida sp. in pregnant women using VITEK-2 - Mishra, Sujata P.; Sahoo, Chita R.; Rath, Siba N.; Padhy, Rabindra N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Candida sp. is seen in several areas of body such as, mouth, groin area including vagina and digestive tract as thrush or gastroenteritis. The slide-culture technique and the VITEK-2 automated system were used for species-identification of the fungus; nonetheless, a gold standard or any first identification method would have inherent errors in arriving at a correct identification of a microorganism at species level. Methods: Morphological fungal criteria were ascertained with germ tubes, glucose agar, sugar fermentation and sugar assimilation tests Candida from vaginal swabs and other clinical samples of 85 infected pregnant women with diabetes, by growing swab lots on Sabouraud’s Dextrose Agar (SDA) plates, the slide culture technique and the VITEK-2 automated system. Results: Of 85 patients, 122 isolates in SDA culture were determined as 7 Candida sp. with number of isolates of each species, as follows: 47 C. albicans, 9 C. famata, 11 C. glabrata, 13 C. guilliermondii, 8 C. krusei, 3 C. parapsilosis and 37 C. tropicalis from vaginal swabs. From 60 vaginal swabs, 46 urine samples and 12 throat swabs it was seen that C. albicans was most prevalent. However, withVITEK-2, 201 fungal strains were identified; Candida sp. was isolated in all samples: 59 C. albicans, 19 C. famata, 21 C. glabrata, 23 C. guilliermondii,18 C. krusei, 13 C. parapsilosis and 48 C. tropicalis. Conclusions: The most prevalent species among the isolated fungi was C. albicans, causing VC in diabetic pregnant women.